2018
DOI: 10.3892/ijo.2018.4318
|View full text |Cite
|
Sign up to set email alerts
|

Asparaginyl endopeptidase enhances pancreatic ductal adenocarcinoma cell invasion in an exosome-dependent manner and correlates with poor prognosis

Abstract: Pancreatic cancer is one of the most lethal types of cancer; owing to low early detection rates and high metastasis rates, it is associated with an extremely poor prognosis. Therefore, a better understanding of the molecular mechanisms that underlie its metastasis and the identification of potential prognostic biomarkers are urgently required. Although high expression levels of asparaginyl endopeptidase (AEP) have been detected in various types of solid tumor, the expression and functions of AEP in pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Also, asparaginyl endopeptidase (AEP), delivered by EVs secreted by PC cells, was shown to promote invasion. Indeed, this protein is able to activate the PI3K pathway in recipient cells leading to increased invasion in vitro [96]. Another protein abundant in PC EVs is the CD44 variant isoform 6 (CD44v6).…”
Section: Pancreatic Cancer and Extracellular Vesicle Proteinsmentioning
confidence: 99%
“…Also, asparaginyl endopeptidase (AEP), delivered by EVs secreted by PC cells, was shown to promote invasion. Indeed, this protein is able to activate the PI3K pathway in recipient cells leading to increased invasion in vitro [96]. Another protein abundant in PC EVs is the CD44 variant isoform 6 (CD44v6).…”
Section: Pancreatic Cancer and Extracellular Vesicle Proteinsmentioning
confidence: 99%
“…Though LGMN is highly expressed in the majority of human solid tumors and is associated with a more invasive and metastatic phenotype, the underlying mechanisms of its tumor-promoting effects have yet to be fully elucidated ( Mai et al, 2017 ). We previously found that high expression of LGMN is involved in the progression of pancreatic carcinoma in an exosome-dependent manner and that LGMN independently indicated poor prognosis; however, the upstream regulation of LGMN remains unknown ( Yan et al, 2018 ). The regulation of gene expression by transcription factors is a common cellular event.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, LGMN has been shown to exhibit a vesicular staining pattern, and high expression of LGMN was significantly related to an advanced tumor stage, a high Gleason score, perineural invasion, and large pancreatic adenocarcinoma tumors ( Zhu et al, 2016 ). Although we previously found that high LGMN expression was involved in the progression of pancreatic carcinoma in an exosome-dependent manner and LGMN could independently indicate poor prognosis, the upstream regulation of LGMN remains unknown ( Yan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specific metabolic enzymes were also transferred by PDA tumor cells-derived EVs. Protease asparaginyl endopeptidase (AEP), expressed in several carcinomas and previously associated with increased metastases and MMP activity, was shown to be transferred via PDA tumor cells derived-EVs and consequently, in recipient PDA tumor cells, increased migratory and invasive capacity, going along with the finding that AEP is usually found at the invasive front of tumors [ 46 ]. Finally, hypoxic PDA cells, with the aid of upregulated HIF-1-alpha, were found to release larger quantities of smaller-sized EVs and promoted their survival even under extremely hypoxic conditions, indicative of yet another communicative aspect of EV structure and cargo between heterogeneous cancer cells [ 47 ].…”
Section: Tumor Cells Evs-mediated Crosstalkmentioning
confidence: 99%